1994
DOI: 10.1111/j.1469-8749.1994.tb11868.x
|View full text |Cite
|
Sign up to set email alerts
|

International Headache Society Criteria and Childhood Headache

Abstract: SUMMARY The objective of this study was to determine whether the intuitive clinical diagnosis of a headache type made by paediatric neurologists would also have fulfilled International Headache Society (IHS) criteria for that type. Clinical information was recorded on data sheets. The neurologists made clinical diagnoses without referring to a fixed set of criteria. An independent physician then used the information on the data sheets to classify the child's headache by IHS criteria. Complete data sheets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 7 publications
4
26
0
Order By: Relevance
“…5,22 For the evaluation of episode intensity, this study shows that behaviour during attacks is a more appropriate measure than pain score, especially for the youngest children; in fact, pain score could not be provided by many children, especially the youngest. In a previous report, 15 behaviour during episodes was found to be a valid measure of intensity compared with a clinician's impression.…”
Section: Discussionmentioning
confidence: 90%
“…5,22 For the evaluation of episode intensity, this study shows that behaviour during attacks is a more appropriate measure than pain score, especially for the youngest children; in fact, pain score could not be provided by many children, especially the youngest. In a previous report, 15 behaviour during episodes was found to be a valid measure of intensity compared with a clinician's impression.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, young children and their parents may not be able to describe the pain or the associated features of the attacks in the terms required by the IHS criteria. For example, in their specialty center-based study, Seshia et al [9] found that in children with headaches, 30% could not describe the quality of their pain and 16% could not report on photophobia and phonophobia. Inability to report migraine-defining features may lead to underdiagnosis using strict IHS criteria.…”
Section: Pediatric Migrainementioning
confidence: 97%
“…The utility of the IHS criteria for pediatric headache disorders has been challenged primarily because expert clinical diagnosis and IHS-based diagnosis often disagree. Reported levels of agreement have ranged from 44% to 66% [5][6][7]9,28,29]. For example, Seshia et al [9] examined a specialty referral sample of 77 children (median age 11 years).…”
Section: Pediatric Migrainementioning
confidence: 98%
See 2 more Smart Citations